Analisis Hubung Singkat Pada Jaringan Tegangan Menengah 20 kV Penyulang Kedonganan - aryamantara, komang jaryanta; Giriantari, I.A.D; Sukerayasa, I.W (Majalah Ilmiah Teknologi Elektro, 2018)
Abstract— In this study, the short circuit simulation conducted of 3-phase, phase to phase and single line to ground fault in several alternate site points which are selected based on the interruption that might occur in the feeders and from the GI base point thought end point in Kedonganan feeders. The value of short circuit current are used to set the time setting of over current relay  to make the protection equipment run according to safety requirements. Based on the analysis result, it shows that the current interruptions are influenced by the distant of interruption, the more distant the point then the smaller short circuit current would happened, and vice versa. The increasing short circuit current can caused a grading time in relay in each alternate location with average grading time about 0,4 second. Rearrangement of protection system in short circuit is recommended especially in protection system based on outcome which can improve the sensitivity and selectivity for  better protection system.